Internal and interface shear strengths of unreinforced and needle-punched geosynthetic clay liners. Issue 3 (June 2004) - Chiu, P.; Fox, P. J.
Abstract : This paper presents information from a large database that has been compiled on internal and interface shear strengths of geosynthetic clay liners (GCLs). The data were obtained from the literature, GCL manufacturers, and the authors' own tests, and are representative of the most common materials and interfaces used in the construction of landfills and other facilities that incorporate GCLs as hydraulic barriers. Internal shear strengths are presented for unreinforced and needle-punched GCLs. Interface shear strengths are presented for needle-punched GCLs placed against smooth geomembranes, textured geomembranes, drainage geocomposites, and soil. Peak and large-displacement shear strengths are reported, along with displacements at peak strength and post-peak strength ratios. The database is useful for: (1) gaining insight into the shear behavior of GCLs; (2) illustrating the variability of GCL shear test results; (3) obtaining preliminary strength parameters prior to conducting project-specific shear tests for final design; and (4) comparing with the results of future shear tests on similar or new GCL products.